2022
DOI: 10.21037/jtd-22-842
|View full text |Cite
|
Sign up to set email alerts
|

EHD2 inhibits the invasive ability of lung adenocarcinoma and improves the prognosis of patients

Abstract: Background: EHD2 may be involved in tumorigenesis and development. However, the role of EHD2 in lung adenocarcinoma (LUAD) is unknown. Methods:The link between EHD2 and LUAD and the associated underlying mechanism was determined using bioinformatics analysis. Then, immunohistochemistry (IHC) was employed to detect EHD2 expression level in LUAD patients. The stable transfection cell line was used to establish with lentivirus vector, and then the transfection efficiency was detected by western blot. Phagokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Recently, reducing the morbidity and mortality of LUAD has been a major global public health concern. Some biomarkers could predict the survival time of LUAD patients and inhibit or promote the progression of LUAD [ [19] , [20] , [21] , [22] ]. EHD2 protein expression is decreased in LUAD and is associated with lymph node metastasis, advanced tumor stage, and decreased survival, as well as being an independent prognostic factor in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, reducing the morbidity and mortality of LUAD has been a major global public health concern. Some biomarkers could predict the survival time of LUAD patients and inhibit or promote the progression of LUAD [ [19] , [20] , [21] , [22] ]. EHD2 protein expression is decreased in LUAD and is associated with lymph node metastasis, advanced tumor stage, and decreased survival, as well as being an independent prognostic factor in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of EHD2 expression promoted the migration and invasion of A549 cells. Overexpression of EHD2 inhibited the migration and invasion of H1299 cells [ 19 ]. The expression of DDR1 in LUAD tissues is higher than that in normal tissues, and DDR1 overexpression is negatively correlated with poor prognosis in LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of various omics technologies and bioinformatics, more and more genes have been identified as biomarkers for certain cancers for disease screening, diagnosis, prognosis, or further development as therapeutic targets corresponding biological reagents. Wei et al found that EHD2 can inhibit the invasive ability of LUAD, improve patient prognosis, and can be used as a prognostic biomarker for LUAD [ 30 ]. Huang et al showed through bioinformatics analysis and cellular experiments that high expression of GRSF1 promotes the occurrence and development of LUAD tumors and can be used as an effective prognostic biomarker for LUAD patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed IHC analysis was conducted according to a previous study ( 24 ). All early-stage LUAD tissues used in this study were placed in liquid nitrogen after surgery.…”
Section: Methodsmentioning
confidence: 99%